Pergaulan Remaja Menurut Pandangan Islam - Irwanto (Al-Fikru: Jurnal Ilmiah, 2019)
This increasingly advanced era with a variety of modern sophistication, especially the development of IT (Science and Technology) is not balanced with the teachings of Islam, then what will happen is the moral and moral destruction of children, especially teenagers. This can be seen from their association that has abandoned religious norms, such as gathering between men and women without limits, many young women who do not wear the hijab, getting away from worship and always close to disobedience. So Islam has provided rules for teenagers to get along and have morals, so that later they can minimize the associations that violate religious norms..